The establishment and refinement of the National Basketball Association Player Injury and Illness Database - Mack, C. D.; Meisel, P.; Herzog, M. M.; Callahan, L.; Oakkar, E. E.; Walden, T.; Sharpe, J.; Dreyer, N. A.; DiFiori, J. (Journal of Athletic Training, 2019)
The National Basketball Association (NBA; also referred to as "the league") has established a centralized, audited electronic medical record system that has been linked with external sources to provide a platform for robust research and to allow the NBA to conduct player health and safety reviews. The system is customized and maintained by the NBA and individual teams as part of the employment records for each player and is deployed uniformly across all 30 teams in the league, thereby allowing for standardized data on injuries, illnesses, and player participation in NBA games and practices. The electronic medical record data are enriched by linkage with other league external data sources that provide additional information about injuries, players, game and practice participation, and movement. These data linkages allow for the assessment of potential injury trends, development of injury-prevention programs, and rule changes, with the ultimate goal of improving player health and wellness. The purpose of this article is to describe this NBA injury database, including the details of data collection, data linkages with external data sources, and activities related to reporter training and data quality improvement.